PENGARUH PENERAPAN E-SPT, PEMAHAMAN PERPAJAKAN DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK DI KPP PRATAMA BATAM SELATAN - Rumahombar, Rani Adelina; L. TOBING, Vargo Christian (LPPM Universitas Putera Batam, 2021)
the purpose of this study was to analysize how much influence the application of E-SPT understanding of taxation and tax service had on tax payer complience at KPP pratama batam selatan. this data collection was done by using a questionnaire which was measured using a Likert scale. the population taken in study are individual taxpayer who have been registered at the KPP pratama batam selatan, totaling 346.849 people and the sampling techniqe is carried out using the slovin formula calculation, from the slovin formula calculation, the number of sample in this study is quantitative data analysis with data collection techniques, namely descrriptive analysis, Validity test, Reability Test, F test, Multiple Linear Regression Test, Normality Test, Multicolinearity Test, Heteroscedastisity Test, F Test, T Test, and Determination Test, the data was processed using the SPSS 25 Application. The result of this study indicate that the variable application of E-SPT has a signifticant efeect on tapayer complience, the variable understanding of taxation has no signifticant effect on taxpayer compliance, and the variable application of E-SPT understanding of taxation, and tax service services together have a signifticant effect on taxpayer compliance at KPP Pratama Batam Selatan.